The betrayal of dissent : beyond Orwell, Hitchens and the new American century - Lucas, Scott (Pluto, 2004)
Since his death in 1950, George Orwell has been canonised as England's foremost political writer, and the standard-bearer of honesty and decency for the honourable 'Left'. In this controversial polemic, Scott Lucas argues that the exaltation of Orwell, far from upholding dissent against the State, has sought to quash such opposition. Indeed, Orwell has become the icon of those who, in the pose of the contrarian, try to silence public opposition to US and U K foreign policy in the 'War on Terror'. Lucas's lively and readable critique of public intellectuals including Christopher Hitchens, Michael Walzer, David Aaronovitch, and Johann Hari - who have all invoked Orwellian honesty and decency to shut down dissent - will appeal to anyone disillusioned with the wars in Afghanistan and Iraq. Lucas contends that these leading journalists and commentators have used Orwell to justify their own political transition from radicals to upholders of the establishment. All of them play influential roles in supporting the UK and US governments' charge that opponents of war -- and those who question the motives behind American foreign policy and its implementation -- should be condemned as 'appeasers of mass murder'. This controversial book shows how Orwell has been used since 9/11 to justify, in the guise of independent thought, the suppression of dissent. We must rescue ourselves from Orwell and from those who take on his guise so, as Lucas puts it, our 'silencing is ... vital to a "manufacture of consent" for the wars which are supposedly being fought in our name and for our good'